Satisfaction Of The Islamic Finance Industry With The Performance Of Interns In Higher Education - Akhmad Baidun; Akhmad Nur Zaroni; Fachrurazi, Fachrurazi; Rihfenti Ernayani (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to estimate the role of tertiary apprenticeship performance in influencing Islamic finance industry satisfaction. By utilizing the results of interviews with 28 Islamic finance practitioners, this study conducted a qualitative analysis. This study found that expectations and disconfirmation factors play an important role in increasing the satisfaction of the Islamic finance industry. Academically, this study implies the expansion of knowledge about industrial satisfaction engineering. Practically, this study implies the importance of link and match between industry and higher education institutions in three ways (uniformity in apprenticeship program assessments, creation of MOUs, and collaboration in curriculum development).